Birch pollen—The unpleasant herald of spring - Raith, Marianne; Swoboda, Ines (Frontiers in Allergy, 2023)
Type I respiratory allergies to birch pollen and pollen from related trees of the order Fagales are increasing in industrialized countries, but the reasons for this increase are still debated and seem to be multifaceted. While the most important allergenic molecules of birch pollen have been identified and characterized, the contribution of other pollen components, such as lipids, non-allergenic immunomodulatory proteins, or the pollen microbiome, to the development of allergic reactions are sparsely known. Furthermore, what also needs to be considered is that pollen is exposed to external influences which can alter its immunogenicity. These external influences include environmental factors such as gaseous pollutants like ozone or nitrogen oxides or particulate air pollutants (e.g., particulate matter), but also meteorological events like changes in temperature, humidity, or precipitation. In this review, we look at the birch pollen from different angles and summarize current knowledge on internal and external influences that have an impact on the allergenicity of birch pollen and its interactions with the epithelial barrier. We focus on epithelial cells, since these are the first line of defense in respiratory disease and are increasingly considered to be a regulatory tissue for the protection against or the development of respiratory allergies.